Collaborative Governance dalam Perluasan Kepesertaan BPJS Ketenagakerjaan di Kota Padang - Trimaulina, Yona; Koeswara, Hendri; Wahyuni, Nila (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
The low level of Universal Coverage Jamsostek (UCJ) in Padang City reflects the limited access to social security protection, particularly for informal and vulnerable workers. This study aims to analyze the collaborative process among stakeholders in expanding BPJS Ketenagakerjaan participation and to identify the supporting and inhibiting factors. A descriptive qualitative method was employed through interviews, documentation, and observations, with data validated using source triangulation. Informants were selected through purposive sampling to ensure the representation of key actors. The findings reveal that the collaboration has not yet produced a significant increase in the number of participants from the informal sector. Nevertheless, the process has fostered equality of roles, stronger commitment, and more open communication among institutions. Theoretically, this research contributes to the development of Collaborative Governance studies by emphasizing the importance of process dynamics rather than solely focusing on outcomes. In terms of policy implications, the results highlight the need to strengthen regulations, provide sufficient budgetary support, and encourage active involvement of local governments to ensure the sustainability of cross-sector collaboration. Thus, efforts to expand social security coverage can become more structured, inclusive, and oriented toward the protection of informal workers who remain highly vulnerable.